Y Yessimsiitova Z., Ablaykhanova N.T., Mankibayeva S.A., Zharkova I.M., Aysabayeva A.E., Aytzhan M.U., Eltay G.E., Mukash A.S., Abdikarimova Y.N. Morphological studying of rats skin in an experiment: Al-Farabi Kazakh national university, Almaty, Kazakhstan *E-mail: zura1958@bk.ru, nurzhanat75@ mail.ru (ҚазҰУ хабаршысы. Экология сериясы, 2017)
The integument of a human body and animals can damage or destroy many substances having thechemical nature. Violations of integrity of integuments can occur under the influence of various factors.The chemical burn of skin is especially aggressive. It can be caused by chemicals and means on their basis. Chemical burns result from influence of acids, alkalis and aggressive substances. A chemical burn ofskin of various parts differ in acids, alkalis or salts of heavy metals on expressiveness degree. Interactionof chemical with protoplasm of cells of tissues is characteristic of them. At effect of acids there is a dehydration of skin which is followed by allocation of heat and overheating of tissues that leads to coagulationof proteins and formation of a dense dry scab. At long influence of elements on integuments, there isa violation of integrity of the last. Extent of defeat depends on concentration of harmful substance andduration of his stay on the surface of skin. Even the low-concentrated solutions can become the cause ofa burn if in time not to notice them. After hit of substance on skin chemical reaction is formed. It causesdestruction of proteinaceous structures of skin, and membrane phospholipids. In this case on a surfacethere are wounds, inflammatory process. Hit of aggressive substance on a surface of an epithelium is resulted by the local chemical reaction leading to a destruction of dermal proteins, phospholipids of membranes. Morphological changes are supplemented with an ulceration of wounds and development ofinflammatory process. All this in total gives an overall picture of the corrosive burn which is shown one offour degrees. In recent years considerably interest of researchers in search of the new materials suitablefor use in the medical purposes, in particular nanosorbents grew. By the present moment approaches totreatment of wounds of a skin are developed. In this regard, undoubted interest for the experts workingin the field represents our research which was referred on studying of local changes of structure of a skinafter influence of a chemical factor with use of medical bandages, possessing antimicrobial action at theexpense of a carbonaceous fiber, activly deleting a pathological microflora from a wound. This scientificexperiment pursued the aim to give a comparative assessment to efficiency of use of a new method fortreatment of combustions of a skin a medical bandage with a sorbent No. 1, No. 2. The sorbent bandageswas a part No. 1 vitamin A, E, the dimined powder 3 gr., camphoric oil of 1 ml, and structure No. 2 thesorbent bandages consisted of the dimined powder 3gr., olive oil of 1 ml., vaselinum of 1 g.Key words: organs, destruction, enterosorbent, histology, morphology, necrosis, pathology